Sistem Pendukung Keputusan Untuk Penentuan Penerima Beasiswa di Universitas Muhammadiyah Surakarta Berbasis Web Dengan Metode Topsis - Sulistyawati, Tri; , Dr. Heru Supriyono, M.Sc; , Drs. Sujalwo, M.Kom (2015)
Scholarship is a form of financial assistance given to individuals who intended to be used for the continuation of education were taken. Universitas Muhammadiyah Surakarta is an institution engaged in education. Each year many offers scholarships provided to students at the Universitas Muhammadiyah Surakarta from various agencies such as the Beasiswa Bantuan Mahasiswa (BBM) and the Cost of Education Scholarship and Beasiswa Dan Bantuan Biaya Pendidikan Peningkatan Prestasi Akademik (BBP-PPA) from Direktorat Pendidikan Tinggi (Ditjen Dikti), Scholarship Toyota Astra, Djarum and others.Everyyearthe number of applicantsscholarships at Universitas Muhammadiyah Surakarta increased and the manager must conduct a selection process that is still using intuition, which is the manager of the scholarship comparing data scholarship applicants then select candidates, so it takes quite a long time. With these considerations, we need a system that can simplify and speed up the selection process based on decision support systems. This study implemented a web-based system with the calculation method decisionsTechnique for order preference by similarity to ideal solution (TOPSIS). The results displayed by the system can provide information to the administrators or managers of the scholarship recipients in accordance with the calculation, then the administrators or managers of the scholarship may announce the recipient of scholarships information online.